Accuracy of the Cameriere´s method and its variant the European Formula for age estimation in subadult Peruvian population - Bravo Molina, Franz Yosset (2022)
Objective: To determine the accuracy of the Cameriere method and its variant, the European Formula, in a sub-adult Peruvian population; and determine a chronological age predictor equation. Materials and methods:  Descriptive, observational, cross-sectional and retrospective study. It was used 257 digital panoramic radiographs of patients in mixed dentition from 5 to 12 years of age belonging to the "Dental Cientifica" Dental Center of the Universidad Cientifica del Sur in the city of Lima, Peru. All morphological variables xi, i= 1,...,7, s, N0 and gender of the subjects were used as predictor variables for age estimation. To evaluate the accuracy of each estimation method, the age of each individual was compared with the estimated age using the mean prediction error. Multiple linear regression was used to generate the predictive equation for chronological age. Results: It was found that the mean prediction error between the chronological age with respect to the age estimated by the Cameriere method Formula and the European Formula was 0.73±0.55 years and 0.77±0.57 years, respectively. A model was generated whose predictor variables for age were s and N0, both variables were statistically significant and the Adjusted R2 for the number of variables was 75.96%. Conclusion: It was determined that Cameriere's Formula was more accurate than the European Formula; however, there was no statistically significant difference between the two. Additionally, it was possible to establish a specific linear regression formula for a Peruvian population aged 5 to 12 years with an adequate predictive capacity.